Development of marketing at agricultural and processing enterprises - Bondarenko, V.; Alekseieva, K.; Havryliuk, Y.; Riabchyk, A.; Tsikhanovska, V.; Barylovych, O.; Chornenka, L.; Karpenko, L.; Lazebnyk, V. (Primedia eLaunch, 2025)
All rights reserved. Printed in the United States of America. No part of this publication may be reproduced, distributed, or transmitted, in any form or by any means, or stored in a data base or retrieval system, without the prior written permission of the publisher. The content and reliability of the articles are the responsibility of the authors. When using and borrowing materials reference to the publication is required.
https://www.researchgate.net/publication/389292206_DEVELOPMENT_OF_MARKETING_AT_AGRICULTURAL_AND_PROCESSING_ENTERPRISES_VOL_2
Keywords: development of marketing; marketing; розвиток маркетингу; маркетинг